Outcomes of laparoscopy‐assisted fetoscopic laser photocoagulation for twin–twin transfusion syndrome: An established alternative for inaccessible anterior placenta. (17th October 2021) - Krispin, Eyal; Nassr, Ahmed A.; Espinoza, Jimmy; Donepudi, Roopali; Sun, Raphael C.; Sanz‐Cortes, Magda; Mostafaei, Shayan; Belfort, Michael A.; Shamshirsaz, Alireza A.
Abstract: Objective: To evaluate laparoscopy‐assisted fetoscopic laser photocoagulation (FLPC) of placental anastomoses in the treatment of twin‐to‐twin‐transfusion syndrome (TTTS). Study Design: We performed a retrospective cohort study analyzing pregnancies complicated by TTTS who underwent FLPC in a single university‐affiliated tertiary medical‐center. Outcomes were compared between patients who received laparoscopy‐assisted FLPC (study group) and patients who underwent the conventional FLPC technique (control group). Baseline characteristics, sonographic findings, procedure details, and neonatal outcomes were compared between groups. Results: The cohort included 278 women with 31 in the study group and 247 in the control group. Sonographic parameters, including fetal biometry and TTTS stage, were comparable between study groups. Gestational age at delivery did not differ between the groups (29.22 ± 4.55 weeks in the study group vs. 30.62 ± 4.3 weeks in the control group, p  = 0.09). There were no differences in neonatal survival rates at birth and at 30 days between both groups. A subanalysis comparing the laparoscopy‐assisted group to only those patients with anterior placenta in the control group, showed a lower rate of incomplete Solomonization in the laparoscopy‐assisted study group (3.4% vs. 33%, p  = 0.01). Conclusion: Laparoscopy‐assisted FLPC is a reasonable and safe option that may be offered in cases of FLPC where an anterior placenta restricts adequate surgical access. Key points: What's already known about this topic? Laparoscopic‐assisted fetoscopic laser photocoagulation should be considered in cases of twin‐to‐twin‐transfusion syndrome with inaccessible anterior placenta. What does this study add? When performed in the setting of a specialized fetal center with expertise, this surgical approach could increase the completion of Solomonization and laser photocoagulation of placental anastomoses.